Efficacy of alertness training in a case of brainstem encephalitis: Clinical and theoretical implications. - Hauke J; Fimm B; Sturm W (Neuropsychological Rehabilitation, 2011)
Although attention functions are often impaired after stroke, traumatic brain injury or inflammatory diseases, little is known about the time course and the long-term efficacy of training-induced improvement. The present single case study evaluates the time course and longitudinal stability of attention improvement after alertness training by repeatedly testing the subject between individual training sessions as well as one and seven months after the end of the training. The outpatient (M.P.) trained developed severe alertness deficits following brainstem encephalitis in 2003 without signs of cortical damage, and since then had not achieved full recovery. In 2008, M.P. participated in 15 treatment sessions on 15 separate working days over a period of three weeks. In each session a 45-minute alertness training task was administered, using the CogniPlus ALERT computer training program. Attention performance was assessed by neuropsychological tests four years, one year, and immediately before the therapy after every third training session and three times after the termination of therapy. Furthermore, a self-report questionnaire measured subjective experience of attention in everyday life situations. In order to compare the performance between training sessions, a procedure specialised for psychometric single-case diagnosis was used to analyse the data. Surprisingly, even after three consecutive training sessions, M.P. showed immense improvement in alertness. Furthermore, after two weeks she felt more energetic and more able to concentrate. Six months after the end of the training the improvement remained stable. The unexpectedly fast time course of recovery induced by the training, as well as the stable long-term effects, probably depend on intact cortical structures. In M.P. it appeared that top-down control of the alertness network on impaired brainstem arousal structures had been re-activated by the training procedure and had remained stable across a long time period.